2011
DOI: 10.1056/nejmoa1008862
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus, Fasting Glucose, and Risk of Cause-Specific Death

Abstract: BACKGROUND The extent to which diabetes mellitus or hyperglycemia is related to risk of death from cancer or other nonvascular conditions is uncertain. METHODS We calculated hazard ratios for cause-specific death, according to baseline diabetes status or fasting glucose level, from individual-participant data on 123,205 deaths among 820,900 people in 97 prospective studies. RESULTS After adjustment for age, sex, smoking status, and body-mass index, hazard ratios among persons with diabetes as compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

50
916
7
18

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,267 publications
(991 citation statements)
references
References 35 publications
50
916
7
18
Order By: Relevance
“…Women had a higher risk of death due to index stroke/recurrent stroke 40.2% versus 33.3%; ns but a lower risk of death due to cancer 5% versus 9%. In patients with increased fasting blood glucose levels/diabetes mellitus, increased mortality rates have been reported (Emerging Risk Factors Collaboration, 2011; Eriksson & Olsson, 2001) as in the present trial where the differences existed mainly for index stroke. Men had a higher risk of death due to cardiosclerosis, heart failure, or arrhythmia versus women ( p  = .014), which could have partly depended on a higher frequency of several MIs.…”
Section: Discussionsupporting
confidence: 50%
“…Women had a higher risk of death due to index stroke/recurrent stroke 40.2% versus 33.3%; ns but a lower risk of death due to cancer 5% versus 9%. In patients with increased fasting blood glucose levels/diabetes mellitus, increased mortality rates have been reported (Emerging Risk Factors Collaboration, 2011; Eriksson & Olsson, 2001) as in the present trial where the differences existed mainly for index stroke. Men had a higher risk of death due to cardiosclerosis, heart failure, or arrhythmia versus women ( p  = .014), which could have partly depended on a higher frequency of several MIs.…”
Section: Discussionsupporting
confidence: 50%
“…Because DM predicts premature mortality of virtually all causes 1, we tested in a next step if baseline plasma furin levels relate to death from any cause. Participants with elevated furin levels at baseline were observed to be at higher risk of death compared to individuals with lower furin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is associated with risk of premature mortality from vascular disease, several cancers and nonvascular causes not attributed to cancer, including digestive diseases, infectious diseases and neurological disorders, independently of major risk factors 1.…”
Section: Introductionmentioning
confidence: 99%
“…Whether this improvement in CHD as a result of risk factor control translates to a reduction in mortality after revascularization has not previously been reported and our observational study provides data from a large cohort suggesting this may be the case and provides stimulus for further research. In addition to macro‐ and microvascular disease, the Emerging Risk Factors Collaboration study reported diabetes to be associated with increased premature death from several cancers, infectious diseases, intentional self‐harm, and degenerative disorders, independent of major risk factors 14. This large cohort study defined baseline diabetes status on the basis of self‐report, medication use, fasting glucose level ≥126 mg/dL [7.0 mmol/L], or a combination of these but did not differentiate mortality on the basis of differences in management strategies.…”
Section: Discussionmentioning
confidence: 99%